Mediasi Komitmen Organisasi Dan Kreativitas Karyawan Dalam Menjelaskan Pengaruh Empowering Leadership Terhadap Task Performance - Wahyuningsih, Sri Handari; Mu’min , Abid Fadhillata (Journal of Science Education and Management Business, 2025)
This study aims to analyze the direct and indirect effects of empowering leadership on task performance through organizational commitment and creativity. The research sample was 171 employees of Putra Baru Swalayan in Central Lampung Regency with non-probability sampling technique. Through SEM-PLS 4.0 analysis technique, the results of the study concluded that empowering leadership cannot directly affect task performance. However, in line with the hypothesis, empowering leadership has a positive effect on organizational commitment. Likewise, empowering leadership has an effect on employee creativity. Also, the results show that organizational commitment has a positive effect on task performance, and employee creativity has a positive effect on task performance. This study proves the mediating role of organizational commitment in explaining the effect of empowering leadership on task performance. Likewise, employee creativity mediates the effect of empowering leadership on task performance through its role as a mediating variable. The results of this study provide implications for the importance of organizations implementing leadership that is able to encourage commitment and creativity so that it can improve performance.